Understanding of Social Media Literacy About Malay Cultural Teaching: A Case Study of Students of SMAIT Al-Ittihad Pekanbaru - M, Trie Khairunnisa; Amelia, Vita; Monika, Winda (Library and Information Science Study Program, Faculty of Humanities, Univ. Diponegoro, 2025)
Background: This research, titled